Intonation on Bornholm - between Danish and Swedish - Grønnum Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1988)
Acoustic investigations of seven speakers on the island of Bornholm and two speakers from Copenhagen, Malmö and Stockholm, respectively, have proved Bornholm to be an interesting compound, prosodically, between Standard Danish and Swedish. A prosodic continuum can be established from Standard Danish, via Skania, over Bornholm, to Standard Swedish. The parameters investigated are (1) manifestation of sentence accent, (2) manifestation of sentence intonation, (3) alignment of fundamental frequency with syllables and segments at the level of the prosodic stress group, and (4) final lengthening. One particularly interesting implication of the results is the division, both according to their function and their form, of sentence accents into (1) prosodically or syntactically determined final default accents and (2) contextually or pragmatically determined focal accents. Default accents are nonexistent in Standard Danish and Skanian, optional in Bornholm and obligatory in Stockholm. Focal accents are non-existent in Standard Danish, optional - but rather rare - in Skanian, optional - but rather frequent - in Bornholm and obligatory in Stockholm.